2013
DOI: 10.1371/journal.pone.0073347
|View full text |Cite|
|
Sign up to set email alerts
|

Cardio-Metabolic Effects of HIV Protease Inhibitors (Lopinavir/Ritonavir)

Abstract: Although antiretroviral treatment decreases HIV-AIDS morbidity/mortality, long-term side effects may include the onset of insulin resistance and cardiovascular diseases. However, the underlying molecular mechanisms responsible for highly active antiretroviral therapy (HAART)-induced cardio-metabolic effects are poorly understood. In light of this, we hypothesized that HIV protease inhibitor (PI) treatment (Lopinavir/Ritonavir) elevates myocardial oxidative stress and concomitantly inhibits the ubiquitin protea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 61 publications
1
37
1
Order By: Relevance
“…Lopinavir/ritonavir tablets were crushed and dissolved in 1% ethanol while sulfamethoxazole/ trimethoprim tablets were crushed and suspended in water [27].…”
Section: Preparation Of Drugmentioning
confidence: 99%
“…Lopinavir/ritonavir tablets were crushed and dissolved in 1% ethanol while sulfamethoxazole/ trimethoprim tablets were crushed and suspended in water [27].…”
Section: Preparation Of Drugmentioning
confidence: 99%
“…2013; Reyskens et al. 2013). Several studies also reported that some PIs are able to induce ER stress in different types of cells (e.g., macrophages, adipocytes, hepatocytes) and tissues (e.g., liver, intestine) (Zhou et al.…”
Section: Introductionmentioning
confidence: 99%
“…PIs are the agents that produce the most adverse effects, but other categories, in particular nonnucleoside/nucleotide reverse transcriptase inhibitors may also influence lipids. 10,[22][23][24] Lipid Changes with Human Immunodeficiency Virus Infection and Antiretroviral Therapy Acute infection lowers low-density-lipoprotein cholesterol (LDL-C), 25 but levels may return to baseline after virologic suppression with ART. 26,27 Chronically, there is often a pattern of low HDL and elevated triglycerides (TG) that results from the metabolic abnormalities (insulin resistance, central adiposity, low HDL, and high TG) clustered in these patients 28,29 and often worsened by specific antiretrovirals, many of which are now less commonly prescribed.…”
Section: Antiretroviral Therapymentioning
confidence: 99%